Crime scene secrets - Black, Maggie K. (Love inspired suspense., 2024)
After shots are fired at a rehearsal dinner, FBI agent Kyle West arrives just in time to chase the gunman away. But attacks persist. Could this be the Rocky Mountain Killer—or a deadly copycat? Now Kyle and his K-9 partner must team up with investigator Ophelia Clarke to hunt down the shooter…before this wedding party becomes a mass murder.